Enhanced Subchondroplasty Treatment for Post‐Traumatic Cartilage and Subchondral Bone Marrow Lesions in a Canine Model. Issue 4 (11th November 2019) - Oliver, Harvey A.; Bozynski, Chantelle C.; Cook, Cristi R.; Kuroki, Keiichi; Sherman, Seth L.; Stoker, Aaron M.; Cook, James L.
ABSTRACT: This study characterizes outcomes associated with subchondroplasty (SCP) versus SCP enhanced with platelet‐rich plasma (PRP) or bone marrow aspirate concentrate (BMC) treatment of impact‐induced subchondral bone marrow lesions (BML) using a validated preclinical canine model. With IACUC approval, purpose‐bred research hounds ( n  = 24) underwent arthroscopic impact injury (40 N) to both medial femoral condyles. At 3 months, functional assessments, arthroscopy, and magnetic resonance imaging (MRI) were performed. One knee in each dog ( n  = 24; n  = 12 per endpoint) was randomly assigned to SCP with the other knee randomly assigned to SCP + PRP, SCP + BMC or sham injection (control) ( n  = 8 per group; n  = 4 per endpoint). Dogs were evaluated at 6 and 12 months after treatment using functional assessments, radiography, arthroscopy, and MRI and humanely euthanatized at 6 or 12 months after treatment for histologic assessments. At 6 months post‐treatment, comfortable range‐of‐motion (CROM) was higher ( p  < 0.04) in SCP + PRP and SCP + BMC knees compared with controls. At 1 year post‐treatment, %Total Pressure Index was higher ( p  = 0.036) in SCP + BMC compared with controls, pain was lower ( p  < 0.05) in SCP + BMC and SCP + PRP compared with SCP and controls, and CROM was higher ( p  < 0.05) in SCP + BMC and SCP + PRP compared with SCP and controls. Knees treated with SCP + PRP and SCP + BMC had better ( p  < 0.05) MRI grades than SCP and controls. No statistically significant differences in arthroscopic or histologic pathology were noted. Clinical significance: Biologics added to SCP treatment may further enhance its beneficial effects by improving range‐of‐motion, pain severity, and limb loading through 1 year after treatment. However, these benefits must be considered alongside cost, logistics, and treatment availability. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:740‐746, 2020